Ammonia flux tailoring on the quality of AlN epilayers grown by pulsed atomic-layer epitaxy techniques on (0 0 0 1)-oriented sapphire substrates via MOCVD - Abd Rahman, Mohd Nazri; Talik, Noor Azrina; Abdul Khudus, Muhammad Imran Mustafa; Sulaiman, Abdullah Fadil; Allif, Kamarul; Zahir, Norhilmi Mohd; Shuhaimi, Ahmad (Royal Society of Chemistry, 2019)
A smooth and dense surface of single-crystalline aluminium nitride thin films has been epitaxially grown on (0 0 0 1)-sapphire substrates by tailoring and optimizing the ammonia flux density during deposition. The aluminium nitride films were deposited by metal organic chemical vapour deposition using the pulsed atomic-layer epitaxy technique at a relatively low growth temperature for ammonia flux densities between 2.2 and 0.2 standard litres per minute (SLM). It is found that the ammonia flux of 0.6 SLM produced the best quality of aluminium nitride films. Field emission scanning electron microscopy as well as atomic force microscopy images revealed a smooth, crack-free and dense surface of aluminium nitride films with the lowest root mean square roughness of 1.61 nm. The in-plane compressive strain inside aluminium nitride films, induced by the hetero-epitaxial growth on sapphire, was examined by focusing on the transition of the E2 (high) peak frequency obtained from the Raman spectra. The lowest threading and mixed-edge dislocation densities were estimated to be 1.50 × 107 and 3.7 × 109 cm−2, respectively, which are comparable to those of state-of-the-art aluminium nitride thin films. © The Royal Society of Chemistry.